PENGARUH MODAL INTELEKTUAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN EARNING PER SHARE SEBAGAI VARIABLE INTERVENING - Ravenski Nadia Friesta, 13.05.52.0199; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2017)
Value of the company describe the good or bad management in managing the company, because of the decisions taken will affect the decisions and impact on the value of the company. The Purpose of this study is to examined the effect of Intelectual Capital and Corporate Social Responsibility to the company value with Earning Per Share as an intervening variable. The samples used in this study is the banking companies listed on the Indonesia Stock Exchange (IDX) on 2013-2015. Based on purposive sampling method obtained by 65 companies. This study used multiple linear regression with path analysis to determine the effect of mediation. The results showed that intellectual capital had positive effect on the Company value and Corporate social responsibility has no effect to the companay value. Earning per share as the mediation variable can’t influence the relation of intelectual capital to the company value.Keywords: Intellectual Capital, Corporate Social Responsibility, Earning Per Share, Company Value